2018
DOI: 10.1061/(asce)hy.1943-7900.0001476
|View full text |Cite
|
Sign up to set email alerts
|

Pipeline Leak Detection Using the Matched-Field Processing Method

Abstract: A transient-based leakage detection method using a matched-field processing (MFP) scheme is formulated and applied. It is found to be efficient, robust, accurate, and provides a unique solution. Its inherent efficiency stems from the fact that the MFP method decouples the search for the leak location and the leak size. Its robustness is demonstrated by showing that the MFP method is able to estimate the location and size of leak in the presence of (1) noise even for signal-to-noise ratio (SNR) as low as SNR ¼ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
66
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 36 publications
(40 reference statements)
2
66
0
Order By: Relevance
“…Consequently, the spacing of potential leaks is advised to be equal to half of minimum wavelength. This result is in agreement with the Nyquist-Shannon theory (Shannon 1949) and recent studies of transient-based leak detection by Wang and Ghidaoui (2018b) that two leaks with a distance lower than half of the minimum wavelength cannot be identified.…”
Section: Spatial Resolution Of Leak Estimatessupporting
confidence: 91%
See 2 more Smart Citations
“…Consequently, the spacing of potential leaks is advised to be equal to half of minimum wavelength. This result is in agreement with the Nyquist-Shannon theory (Shannon 1949) and recent studies of transient-based leak detection by Wang and Ghidaoui (2018b) that two leaks with a distance lower than half of the minimum wavelength cannot be identified.…”
Section: Spatial Resolution Of Leak Estimatessupporting
confidence: 91%
“…In addition, the CRLB shows that the larger the value of J (number of measured frequencies), the smaller the variance of the leak estimate. This dependence on frequency provides a theoretical support for the intuitive result that sharper transients (wider frequency bandwidth) result in more reliable (accurate) defect detection and agrees with the results found by Lee et al (2013Lee et al ( , 2015, Zhao et al (2018), Louati et al (2017), and Wang and Ghidaoui (2018b).…”
Section: Crlb and Its Role In Transient-based Defect Detectionsupporting
confidence: 86%
See 1 more Smart Citation
“…Wang and Ghidaoui (2018a) showed that the modal-interdependence terms for multiple leaks involve products of the usually small leak sizes and used this fact to arrive at a linear relation between measured pressure head and unknown parameters of the leaks. Based on this expression, Wang and Ghidaoui (2018b) proposed a matched-field processing (MFP) approach able to identify a leak based on a 1D search of leak location along the pipe independent of the leak size, which was proven to be robust with respect to a high level of noise. However, it was found that the presence of local maxima in the objective function of MFP may interfere with the judgment of leak location.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, three beamforming techniques (Bartlett's, Capon's, and Lagunas' BFs) and a subspace-based method [multiple signal classification (MUSIC)] are used for pipeline leak localization. Bartlett's BF is equivalent to the MFP method of Wang and Ghidaoui (2018b), which has the drawback that its objective function has high local maxima. The present paper generalizes that method to derive other versions of spectral-based methods, which are able to obtain a unique leak localization.…”
Section: Introductionmentioning
confidence: 99%